Well-Being at Home During Forced Quarantine Amid the COVID-19 Pandemic - Krajewska-Kułak, Elzbieta; Kułak-Bejda, Agnieszka; Kułak, Wojciech; Bejda, Grzegorz; Łukaszuk, Cecylia; Waszkiewicz, Napoleon; Cybulski, Mateusz; Guzowski, Andrzej; Fiłon, Joanna; Aniśko, Paulina; Popławska, Magda (Frontiers in Psychiatry, 2022)
Introduction: People recently or currently in forced quarantine or isolation at home have shown high levels of depression and symptoms of generalised anxiety. Aim of the study: To assess the impact of the COVID-19 pandemic on certain aspects of people’s day-to-day functioning. Materials and methods: The study involved using an online diagnostic survey including a proprietary questionnaire, the DASS 21, and the Liebowitz Social Anxiety Scale. Results: Information about the pandemic in Poland and around the world was systematically obtained by 48.8% and 27.4% of respondents, respectively (N = 1312). Whereas 75.6% of respondents declared having knowledge about the number of infected people in Poland, only 28.7% declared having such knowledge about infections worldwide. Most often, respondents had obtained information online (65.9%). According to 45.7% of respondents, infection with COVID-19 is a major threat and not enough has been done to reduce its spread in Poland (66.7%) or worldwide (56.1%). Respondents considered social distancing (68.3%), quarantining people arriving from abroad (63.4%), and wearing protective masks and/or gloves (60.4%) to be the most effective actions for combatting the pandemic. Most often, in compulsory quarantines, respondents surfed the Internet (48.8%) and experienced a lack of energy or fatigue (40.2%) and anxiety (54.9%). The severity of anxiety (mean = 4.6 points), stress (7.5 points), and depression (7.3 points) were within normal ranges, and the respondents could generally be included in the group showing mildly severe social phobia (57.9 points). Conclusions: Most respondents considered infection with COVID-19 to be a major threat and feared another quarantine. During quarantine, respondents most often experienced fatigue, a lack of energy, nervousness, anxiety, anger, and sadness. Despite demonstrating anxiety, stress, and depression with severity in the normal range, respondents showed no statistically significant correlation between severity and age, gender, place of residence, or level of education. Although they also showed mildly severe social phobia, only gender, not age, place of residence, or level of education, showed a statistically significant correlation with its severity.